Yahoo Web Search

  1. Ad
    related to: K
  1. ... 6/( k +1) - 1/( k ) = 1 ← note: k ≠ 0 or -1 or 6( k ) - ( k +1) = ( k +1)( k ) or 6k - k - 1 = k² + k or 0 = k² + k - 6k + k ...4*3 ) ] / 2 k = [ 4 ± 2√3 ) ] / 2 k = 2 ± √3 k = { 2 - √3, 2 + √3 } k ~ { 0.2679, 3.7321 }

    3 Answers · Science & Mathematics · 11/09/2010

  2. k = ( k +15)/3*( k -1) ==> multiply both sides by 3( k -1) to get rid of fractions 3k( k -1) = k +15 ==> expand the LHS 3k^2-3k = k +15 ==> move everything to the LHS 3k^2-4k-15=0 actually this does...

    3 Answers · Science & Mathematics · 21/07/2007

  3. 2kx² - 12x + ( k +7) = 0 Solve for k b² - 4ac = 0 (b = -12, a = 2k and c = k ...8 ..........-k² - 7k + 18 = 0 .......... k² + 7k - 18 = 0 ........ ( k - 2) ( k + 9) = 0 ...... k - 2 = 0.......................... k + 9 = 0 k - 2 + 2 = 0 + 2...

    4 Answers · Science & Mathematics · 12/09/2010

  4. Sources of Vitamin K Vitamin K is found chiefly in leafy green ...of vitamin K .[7]. Some vegetable oils, notably soybean, contain vitamin K , but at levels that would require relatively large caloric consumption to meet the...

    9 Answers · Food & Drink · 07/03/2009

  5. If k -2 divides 2k, k -2 ≠ 0, then there is an integer i such that 2k = ( k -2)i Solving for k gives... of i less than or equal to 1 that produce k ≥ 3. Therefore the only ...

    1 Answers · Science & Mathematics · 20/03/2009

  6. ∫(x = 0 to 1) x^ k ln x dx = ∫(∞ to 0) (e^w)^ k * w * (e^w...;==> x = e^w = -∫(w = 0 to ∞) we^(( k +1)w) dw = -∫(w = 0 to ∞) we^(( k +1)w) dw...1)t))] = (-1/( k +1)^2) * [1 + lim(t→∞) -e^(( k +1)t)] = (-1/( k +1)^2) * (1 + 0), since k +1...

    3 Answers · Science & Mathematics · 10/06/2015

  7. (2 k +1) * (2k) * (2k-1) * ... * ( k +2) * ( k +1) / 2 = (2k+1) * k * [(2k-1) * ... * ( k +2) * ( k +1)] In...ellipsis notation from becoming ambiguous. (Otherwise the k factor is out of sequence and makes that notation unclear.)

    1 Answers · Science & Mathematics · 18/07/2011

  8. K -9/27 =7/9 Step 1, Multiply 27 to the whole entire problem. 27( K -9/27 =7/9) 27K - 9 = 21 Step 2, Add 9 and Divide...

    2 Answers · Science & Mathematics · 05/05/2012

  9. C= K (Rr/R-r) Divide both sides by K : C...r): (R-r)(C/ K ) = Rr Distribute C/ K : CR/ K -Cr/ K = Rr Subtract Rr...

    4 Answers · Education & Reference · 05/10/2009

  10. k * 3^ k = 1,000,000,000 Start by taking the natural logarithm of both sides of the equation to remove that variable from the exponent:*** ln(3^ k )( k ) = ln(1,000,000,000) Now the exponent of a factor here can be ...

    1 Answers · Science & Mathematics · 21/09/2008

  1. Ad
    related to: K
  1. Try asking your question on Yahoo Answers